PREVALENCE OF HUMAN PARVOVIRUS B19 IgG AND IgM ANTIBODIES AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINIC AT FEDERAL TEACHING HOSPITAL IDO-EKITI, NIGERIA - Akele, Richard Yomi; Abelekum, Jennifer Tamuno; Oluboyo, Bernard Oluwapelumi; Akinseye, Janet Funmilayo; Enitan, Seyi Samson; Olayanju, Olusola Ayodeji; Jide Akele, Olayanju Emmanuel (African Journal of Infectious Diseases (AJID), 2021)
Background: Human Parvovirus B19 (B19V) is a DNA virus, transmitted through respiratory secretions, hand-to-mouth-contact, blood transfusion and trans-placental transfer. It causes high mortality and morbidity in pregnant women, thus contributing to poor maternal and child health. B19V has been neglected due to dearth of epidemiological data. The aim of this study was to determine the sero-prevalence of Human Parvovirus B19 antibodies among pregnant women attending antenatal clinic at Federal Teaching Hospital Ido-Ekiti, Nigeria. Materials and Methods: This cross-sectional study enrolled pregnant women attending Federal Teaching Hospital Ido-Ekiti from January to May 2019 to obtain sero-epidemiological data. One hundred and twenty-two (122) consenting pregnant women were enrolled following institutional ethical approval. They were administered structured questionnaire and venous blood was collected in plain tubes for serum extraction. Sera samples were analyzed for IgG and IgM antibodies using the enzyme linked immunosorbent assay method. Percentages, median, chi-square and multivariate analysis were carried out using SPSS version 17. Results: The prevalence of IgG was 44.3%(54/122), IgM 41.8%(51/122), and IgG/IgM 28.7%(35/122) leaving 55.7%(68/122) of the population uninfected. The median age of participants was 22 (Interquartile range 18-25) years among which 36-45years had the highest prevalence which was not statistically significant (p=0.09 4.75). There was association between miscarriage, still birth, history of blood transfusion and prevalence of Human Parvovirus B19 (p<0.05). Conclusion: There is a high Prevalence of B19V among pregnant women attending antenatal clinic in this study. This underscores the need for testing and immunization of pregnant women against B19V.